New Photochrome Probe Allows Simultaneous pH and Microviscosity Sensing - Wu, Yuanyuan (2017)
4-N,N′-dimethylamino-4′-N′-stilbenemaleamic acid (DASMA), a unique molecular photochrome probe that exhibits solubility and retains trans-cis photoisomerisation in a wide range of organic solvents and aqueous pH environments, was prepared, purified and chemically characterised. Absorption, fluorescence excitation and emission spectra and constant-illumination fluorescence decay were measured in acetonitrile, dimethyl sulfoxide, ethanol, propylene carbonate, and aqueous glycerol mixtures. The pseudo-first-order fluorescence decay rates were found to be strongly dependent on the medium viscosity. In addition, the molecule exhibited the pH-dependent fluorescence and photoisomerisation kinetics.